2007
DOI: 10.1111/j.1365-2362.2007.01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin therapy improves exercise oxygen uptake kinetics in post‐myocardial infarction patients

Abstract: Background Statins represent a modern mainstay of the drug treatment of coronary artery disease and acute coronary syndromes. Reduced aerobic work performance and slowed VO 2 kinetics are established features of the clinical picture of post-myocardial infarction (MI) patients. We tested the hypothesis that statin therapy improves VO 2 exercise performance in normocholesterolaemic post-MI patients. Materials and methodsAccording to a double-blinded, randomized, crossover and placebocontrolled study design, in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…There are also sparse data on the effects of statins on aerobic exercise performance. Atorvastatin improves oxygen uptake kinetics in post–myocardial infarction patients 13 but decreases maximal oxygen uptake in myopathic patients 14 . Interestingly, in the latter study, the resting respiratory exchange ratio (RER; an index of fat and carbohydrate metabolism) increased with statin therapy in both asymptomatic and symptomatic statin users, consistent with other reports suggesting that statins decrease or impair fat oxidation 15–17 .…”
Section: Study Rationalesupporting
confidence: 87%
“…There are also sparse data on the effects of statins on aerobic exercise performance. Atorvastatin improves oxygen uptake kinetics in post–myocardial infarction patients 13 but decreases maximal oxygen uptake in myopathic patients 14 . Interestingly, in the latter study, the resting respiratory exchange ratio (RER; an index of fat and carbohydrate metabolism) increased with statin therapy in both asymptomatic and symptomatic statin users, consistent with other reports suggesting that statins decrease or impair fat oxidation 15–17 .…”
Section: Study Rationalesupporting
confidence: 87%
“…In addition, it is known that reperfusion after ischemia leads to increased production of ROS, mitochondrial permeability and cardiovascular death (26). Thus, according to the intolerance of exercise and oxygen uptake reduction (VO2) in patients with MI (27), and also with regard to the incidence of hypoxia, coronary hypotension, cardiac hyperactivity and excessive oxidative stress, as well as reperfusion following isoprenaline-induced ischemia (20,22,26), it seems that the accumulation of the effects of endurance exercise training and isoprenaline and stress of more dealing with electric shock sticks in training group rats, in the beginning of the exercise protocol in the present study creates more damage in cardiac tissue of endurance training group rats compared with the control group. Therefore, it is likely that the extent of damage in the endurance training group was more than the control group at the first.…”
Section: Discussionmentioning
confidence: 99%
“…Guazzi reported atorvastatin therapy for 3 months in patients with post-myocardial infarction improved FMD in brachial artery and VO 2 max. The authors reckoned the improvement of endothelial function implicated the beneficial therapeutic property of statin in increment of VO 2 max [10]. It has been demonstrated that FMD correlated with VO 2 max in healthy adults and the elderly [8], [9], and the value of FMD of the older athletes was comparable with that of the sedentary young group.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the sedentary elderly, regular physical activities improved the elderly athletes' FMD and VO 2 max [9]. Furthermore, it has been reported that the improvement of endothelial function implicated increase of exercise oxygen uptake during atorvastatin therapy for patients with post myocardial infarction [10]. Based on these studies and the correlation between endurance capacity and cardiovascular fitness, it is reasonable to hypothesize that there may be a relationship between endurance capacity and the endothelial function in university students.…”
Section: Introductionmentioning
confidence: 95%